Mechlorethamine, vincristine, melphalan and prednisolone rescue chemotherapy protocol for resistant feline lymphoma. Issue 10 (October 2018) - Martin, Olya A; Price, Josh
Objectives: The goals of this retrospective study were to evaluate the use of mechlorethamine, vincristine, melphalan and prednisolone (MOMP) chemotherapy for rescue of feline lymphoma, to describe the protocol's toxicity and to determine prognostic indicators for progression-free survival. Methods: The medical records of 12 cats treated with MOMP chemotherapy at the University of Tennessee Veterinary Medical Center between 2007 and 2017 were evaluated. Parameters assessed included lymphoma cell size, anatomical location, number of previous chemotherapy drugs and number of previous rescue protocols received. Chemotherapy-related toxicity was also described. Results: Seven of 12 cats responded to this rescue protocol. Three cats experienced complete response and four cats achieved partial response for a median duration of 39 days (range 14–345 days). Cats that achieved complete response had a significantly longer median progression-free survival than cats that did not respond to treatment. Five of 12 cats developed hematologic toxicity (neutropenia) and one cat developed gastrointestinal toxicity. Toxicity was mild in most cases; no cats needed to be hospitalized. Neutropenia was associated with increased progression-free survival. Conclusions and relevance: MOMP is a safe and effective rescue chemotherapy protocol for cats with relapsing and refractory lymphoma.